Child Care Workers - Gibson, Bush Karen; Shaw, Megan (Mankato: Capstone Press, 2001)
Introduces the responsibilities, equipment, necessary schooling, and different kinds of people who take care of children.
Includes bibliographical references (p. 24) and index.
Keywords: Child care workers -- Juvenile literature; Child care workers; Occupations